Analisis Empiris Faktor Determinan Struktur Modal Perusahaan Infrastruktur Indonesia - Alexandra Christivera; Desya Gunawan; Donna Jovita Fendi (Jurnal Manajemen dan Organisasi, 2019)
The Infrastructure Industry has become the focus of the state expenditure budget during the Joko Widodo-Jusuf Kalla presidency. This is due to the importance of infrastructure in assisting the sustainability of a country's development, but the fact is that government funds as a source of infrastructure funds are delayed when the company has acquired a new project resulting in the use of debt in infrastructure companies as a capital structure to run the new project. The study identifies examination on the impact of capital structure determinants on firm financial performance of Indonesia’s Infrastructure Companies listed over the period of 2014-2018. Determination of the number of samples in this study using non-probability sampling, specifically purposive sampling method. The study uses one capital structure measures (Leverage) as dependent variable and four performance measures (including company’s size, the tangibility of asset, liquidity, and asset turnover) as independent variables and proceed using multiple regression model. The result indicates that liquidity has a significantly negative relationship to leverage, meanwhile company’s size, the tangibility of asset, and asset turnover are not significantly related to the level of debt in infrastructure companies in Indonesia, however, it goes along with the way of thinking in the Pecking Order Theory.